Hahn-Banach Theorem for Normed Spaces - Ferreira, M. A. M. (2017)
This paper main objective is to present two separation theorems, important consequences of the HahnBanach Theorem applied to normed vector spaces. They are very important optimization tools in a lot of problems, namely in economic and management problems.